2019
DOI: 10.1080/17435390.2019.1592259
|View full text |Cite
|
Sign up to set email alerts
|

Systematic determination of the relationship between nanoparticle core diameter and toxicity for a series of structurally analogous gold nanoparticles in zebrafish

Abstract: Systematic determination of the relationship between nanoparticle core diameter and toxicity for a series of structurally analogous gold nanoparticles in zebrafish

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 65 publications
(88 reference statements)
0
17
0
1
Order By: Relevance
“…ENM surface area has been linked to overall toxic response, with the most notable reasoning being the availability of a larger surface area for interactions when the mass per volume is held constant (Lee et al, 2018;Truong et al, 2019). We observe that the two ENM with the highest surface area, 1%Ag-SiO 2 and 10%Ag-SiO 2 exhibit the highest toxicity values.…”
Section: Variable Wagge Responses Across Pcc Reveal Intricate Characteristic Interactions For Toxicity Responsementioning
confidence: 82%
“…ENM surface area has been linked to overall toxic response, with the most notable reasoning being the availability of a larger surface area for interactions when the mass per volume is held constant (Lee et al, 2018;Truong et al, 2019). We observe that the two ENM with the highest surface area, 1%Ag-SiO 2 and 10%Ag-SiO 2 exhibit the highest toxicity values.…”
Section: Variable Wagge Responses Across Pcc Reveal Intricate Characteristic Interactions For Toxicity Responsementioning
confidence: 82%
“…Zebrafish exposure to solid pigments analysis followed analysis in Troung et al [ 63 ]. Embryo Photomotor Response (EPR) behavior was analyzed by comparing the background, excitatory, and refractory intervals to the negative control (0 Îźg/mL of compound) activity using a combination of percent change and a Kolmogorov–Smirnov test (Bonferroni-corrected p -value threshold).…”
Section: Methodsmentioning
confidence: 99%
“…Concentration response modeling based on mortality and morphology data was carried out on mortality data at 24 hpf and at 120 hpf for tested compounds showing significant responses compared to the control. R was used to fit a Hill model to the average of all individuals at each exposure concentration following methods in Truong et al [ 63 ], using the four parameters of lower limit, upper limit, the median effective concentration (EC50) curve inflection point, and the “Hill” slope. Curves were fit with the drm() function in drc package in R, using least squares estimation.…”
Section: Methodsmentioning
confidence: 99%
“…A theme commonly addressed in these studies has been the nature of the relationships between different characteristics and toxicity/bioaccumulation. NM properties have been shown to influence toxicity in case studies with NM sets varying in their compositional chemistry, [ 2,3 ] size [ 4–6 ] and surface coating/charge, [ 7–9 ] allowing potential relationship between measurable structural particle properties and hazard to be proposed. However, not all such studies with differing NMs have found such relationships.…”
Section: Introductionmentioning
confidence: 99%